2010
DOI: 10.1002/cjoc.201090377
|View full text |Cite
|
Sign up to set email alerts
|

Isomeric Effect on H/D Exchange of Resveratrol Studied by NMR Spectroscopy

Abstract: Resveratrol (3,5,4'-trihydroxylstilbene), a phytoalexin in response to injury or fungal attack, is found in grapes and other food products. It has been well documented that the compound has beneficial effects as hypolipidemic, anticancer, antiviral, neuroprotective, antiaging, and anti-inflammatory natural active principle. It was observed that both trans-and cis-resveratrols undergo hydrogen-deuterium (H/D) exchange at H-2,6 and H-4 positions of the A-ring. The exchange rates were determined by 1 H NMR spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…The magnetic moment µ eff in solution was determined to µ eff = 4.84µ B , which accounts for four unpaired electrons per chromium atom. Our results and the molecular structure obtained from XRD are in agreement with the molecular structure reported previously by Zhu et al 28 [{Cr(IMe Me ) (THF)Cl(µ-Cl)} 2 ] defied isolation, but attempts to isolate this complex by crystallization lead to formation of small amounts of a number of single crystals suitable for XRD. The resulting molecular structures reveal that the situation is most probably more complicated as different isomers have been characterized, either isolated molecules [{Cr(IMe Me )(THF)Cl(µ-Cl)} 2 ] (ESI, Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The magnetic moment µ eff in solution was determined to µ eff = 4.84µ B , which accounts for four unpaired electrons per chromium atom. Our results and the molecular structure obtained from XRD are in agreement with the molecular structure reported previously by Zhu et al 28 [{Cr(IMe Me ) (THF)Cl(µ-Cl)} 2 ] defied isolation, but attempts to isolate this complex by crystallization lead to formation of small amounts of a number of single crystals suitable for XRD. The resulting molecular structures reveal that the situation is most probably more complicated as different isomers have been characterized, either isolated molecules [{Cr(IMe Me )(THF)Cl(µ-Cl)} 2 ] (ESI, Fig.…”
Section: Resultssupporting
confidence: 91%
“…It was reported previously that the reaction of CrCl 2 with two equivalents IiPr Me afforded a the chromium complex [Cr (IiPr Me ) 2 Cl 2 ], whereas the reaction using just one equivalent led to formation of dinuclear [{Cr(IiPr Me )(THF)Cl(µ-Cl)} 2 ], which can be regarded as intermediate in the formation of the former. 28,29 We can confirm these results for all NHCs used in this study. The reactions of freshly prepared [CrCl 2 (THF) 2 ] with one equivalent of the free carbenes IMe Me , IiPr Me , IMes, IDipp, and cAAC Me led immediately to intensely blue colored solutions, which obtain their color from initially formed chloride bridged dimers of the type [{Cr(L)(THF)Cl(µ-Cl)} 2 ] or [{Cr(L)Cl (µ-Cl)} 2 ] (L = NHC, cAAC Me ), respectively.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…It has been suggested that the mechanism of H/D exchange reaction of aromatic C-H protons in acid or basic conditions of polyphenolic compounds [37][38][39][40][41] follows a two-step process, 41 as shown in Fig. 2.…”
Section: Nmr Studiesmentioning
confidence: 99%
“…Fireworks and firecracker is one of the most well-known consumer goods around the world. The heavy metal contamination coming from fireworks and firecracker 1,2 is of increasing concern because of its great threaten to human health [3][4][5] . Lead, mercury and chromium identified as highly toxic elements will be gradually accumulated in organism body and further threaten human health through food chains.…”
Section: Introductionmentioning
confidence: 99%